Application of Discovery Learning Model in the Ta'lim Muta'alim Book Study - Rina Dian Rahmawati; Rika Munika (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to determine and obtain information about the application of the discovery learning model in learning the book ta'lim muta'alim in Islamic boarding school riyadlul jannah pasuruan. This study used a qualitative method with the research subjects or the informants used were ustadzah (guru diniyah) and students of grade V, so that researchers obtain appropriate and relevant information. With data collection techniques used were interviews, checking the validity of the data used were direct observation and interviews. Based on the research results, it was found that according to the informant the application of the discovery learning learning model in the learning of the ta'lim muta'lim book was the planning stage which included: 1) Formulating objectives; 2) Develop plans for learning activities; 3) Creating a discovery learning model that will be implemented; 4) Determine time management according to a predetermined schedule; 5) During discovery learning, the ustadzah (teacher) monitors directly so that learning remains conducive and orderly; 6) Ustadzah (teacher) continues to provide additional explanations and conclusions at the end of the lesson. And at the implementation stage includes: 1) stimulation; 2) problem statement; 3) information gathering; 4) proof; 5) conclusion. And in the application found supporting and inhibiting factors. Supporting factors: students are increasingly active in participating in learning and more often come up with new ideas that they can convey or convey. While the inhibiting factor of students is not ready to accept assignments in book learning because book learning is indeed difficult and usually in learning more teachers as a source of information.